Stem Cell-Derived Extracellular Vesicles and Immune-Modulation - Burrello, Jacopo; Monticone, Silvia; Gai, Chiara; Gomez, Yonathan; Kholia, Sharad; Camussi, Giovanni (Frontiers in Cell and Developmental Biology, 2016)
Extra-cellular vesicles (EVs) are bilayer membrane structures enriched with proteins, nucleic acids and other active molecules and have been implicated in many physiological and pathological processes over the past decade. Recently, evidence suggests EVs to play a more dichotomic role in the regulation of the immune system, whereby an immune response may be enhanced or supressed by EVs depending on their cell of origin and its functional state. EVs derived from antigen (Ag)-presenting cells for instance, have been involved in both innate and acquired (or adaptive) immune responses, as Ag carriers or presenters, or as vehicles for delivering active signalling molecules. On the other hand, tumor and stem cell derived EVs have been identified to exert an inhibitory effect on immune responses by carrying immuno-modulatory effectors, such as transcriptional factors, non-coding RNA (Species) and cytokines. In addition, stem cell-derived EVs have also been reported to impair dendritic cell maturation and to regulate the activation, differentiation and proliferation of B cells. They have been shown to control natural killer cell activity and to suppress the innate immune response. Studies reporting the role of EVs on T lymphocyte modulation are controversial. Discrepancy in literature may be due to stem cell culture conditions, methods of EV purification, EV molecular content and functional state of both parental and target cells. However, mesenchymal stem cell-derived EVs were shown to play a more suppressive role by shifting T cells from an activated to a T regulatory phenotype. In this review we will discuss how stem cell-derived EVs may contribute towards the modulation of the immune response. Collectively, stem cell-derived EVs mainly exhibit an inhibitory effect on the immune system.